Toxocara canis myelitis involving the lumbosacral region: a case report - Hiramatsu, Yu (J Spinal Cord Med, 2017)
CONTEXT: Toxocara canis is a parasite known to cause visceral larva migrans. The infection rarely affects the central nervous system but there have been several reports of myelitis caused by visceral larva migrans due to Toxocara canis. In previous reported cases, the lesions were located in the thoracic or cervical spinal cord. To the best of our knowledge, this is the first report of a lesion involving the lumbosacral region. FINDINGS: A 60-year-old man developed weakness and dysesthesia in the lower limbs. The symptoms resolved spontaneously, but recurred after five months. One month later, the patient developed pollakiuria and constipation. He was a dog owner and frequently ate raw chicken meat and beef liver. Sagittal T2-weighted image (T2WI) showed swelling and hyperintensity in the spinal cord from T10 to the lumbosacral region and focal nodular enhancement on the posterior segment of the lumbar spinal cord. Blood cell counts showed slight eosinophilia and elevated serum immunoglobulin E level. Cerebrospinal fluid examination showed slight pleocytosis with eosinophilia. Enzyme-linked immunosorbent assay showed high levels of anti-Toxocara antibodies in the serum and cerebrospinal fluid. In addition, confirmatory test by Western blot was positive. The patient was initially treated with intravenous methylprednisolone with slight improvement in muscle weakness. Albendazole was added with a second course of intravenous methylprednisolone. The muscle weakness in the lower limbs improved considerably, and swelling and hyperintensity on T2WI almost disappeared. CONCLUSION: Our results suggest that Toxocara canis myelitis cannot be discounted even if the myelitis involves the lumbosacral region.